Study of multidirectional forging and annealing on copper - Lim, Zi Xin. (2009)
The use of macroforming technology to produce microproducts has problem such as poor mechanical properties and rough surface due to relatively large grains and fewer grain boundaries. Hence, there is a need to achieve grain refinement in materials in order to have better properties and yet is cost-effective for mass production.